Assessment of bronchiectasis by computed tomography. Issue 12 (December 1985) - Mootoosamy, I M; Reznek, R H; Osman, J; Rees, R S; Green, M
Abstract : Computed tomography and bronchography were used to assess the distribution of bronchiectasis in 15 lungs from eight patients with clinical features of the disease. Of the 36 lobes adequately displayed by bronchography, 22 were found to have bronchiectasis and 14 were found to be normal by both techniques. Cystic disease was readily identified by computed tomography but the cylindrical and varicose types of bronchiectasis could not be distinguished. Segmental localisation was less accurate, with agreement between computed tomography and bronchography in 116 out of 130 segments. It is concluded that with a modern high resolution scanner computed tomography provides a useful method of assessing lobar distribution in bronchiectasis.